RPLUGIN.ECONOMETRICS: PAKET GRAPHICAL USER INTERFACE OPEN SOURCE UNTUK ANALISIS RUNTUN WAKTU MENGGUNAKAN PERANGKAT LUNAK R - Dedi Rosadi; Adi Marhadi (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2009)
R (R Development Core Team, 2009) is one of the open source software that is popular and has become